2016
DOI: 10.4103/2229-5151.183024
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic brain injury: Does gender influence outcomes?

Abstract: Background:Traumatic brain injury (TBI) is a major public health problem. Both genders are affected, but little is known about female TBI. The present study exclusively explores epidemiological, clinical, imaging, and death aspects of female TBI, and how it differs from males.Methods:It is a retrospective study. Data were documented from a tertiary institute during January 2010 to March 2010. All variables were documented on standard proforma. The data were analyzed using R statistics software. Age group was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
76
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(87 citation statements)
references
References 12 publications
6
76
1
4
Order By: Relevance
“…This reflects partially nonrandomized study populations that were self‐selected and included participants of particular subpopulations. Previous studies have shown that gender influences response of brain and outcome following a TBI . One study showed that female and male TBI groups differed significantly in the severity of injury and in mortality .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects partially nonrandomized study populations that were self‐selected and included participants of particular subpopulations. Previous studies have shown that gender influences response of brain and outcome following a TBI . One study showed that female and male TBI groups differed significantly in the severity of injury and in mortality .…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] One study showed that female and male TBI groups differed significantly in the severity of injury and in mortality. 46 Furthermore, it was shown by another study that after concussions, female athletes exhibited lower performance on visual memory composite scores and yielded higher scores on total symptoms compared to male athletes. 48 Of the in vivo studies all but one 20 used an agematched control group.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being comorbidities, GCS and ISS have been well recognized as independent risk factors for mortality due to TBI [24,25,26,27]; gender and BAC also may have a significant effect on the mortality of patients who sustained TBI [28,29]. In a retrospective study of 1627 TBI patients, female patients had a significantly higher mortality (3.4% vs. 1.6%, p = 0.048) [30]. Patients who consumed alcohol tended to experience lower moderate-to-severe TBI injuries [31].…”
Section: Discussionmentioning
confidence: 99%
“…Studies included a range of participant demographics and injury severities, aetiologies, and locations. As males are more likely to sustain brain injuries (Munivenkatappa et al 2016), and the majority of participants in the studies reviewed were drawn from the military population, the gender bias was not unexpected. Readers should therefore interpret this review considering the impact of these factors on impairment profiles and the generalization of the results.…”
Section: Limitationsmentioning
confidence: 99%